International Legal Protection of The Impact of State Activities In Space For Other Countries - Syeni Angel Pattiasina; Wilshen Leatemia; Welly Angela Riry; Richard Marsilio Waas (Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Remote sensing is a natural identification system method or determination of the condition of objects on the earth's surface as well as goods beneath or above it, with suggestions for observations from the air and space. The consequences that are detrimental to the country in the absence of regulation in the use of data and information from remote sensing results from satellites in the economic field are closely related to welfare issues.Purposes of the Research: The purpose of this research is to know and understand the regulation of remote sensing in international law and the impact of its use on other countries.Methods of the Research: This research is a normative study using a statutory approach with the source of legal materials used primary legal materials and secondary legal materials and tertiary legal materials with qualitative analysis with deductive and inductive methods.Results of the Research: The impact of state activities in space, in this case, remote sensing activities, is very beneficial for human life because remote sensing with satellites can cover large areas in a short time. However, on the other hand, these activities can cause a detrimental effect on the countries being sensed, or the under-country, whether in the economic, political, or state defense and security (military) fields because they are related to the sovereignty of the under-country based on international law.